Low grade fibromyxoid sarcoma of the falciform ligament: a case report - Harish, K (BioMed Central, 2003)
BACKGROUND: Low grade fibromyxoid sarcomas (LGFMS) are very rarely seen. They commonly arise from deep soft tissues of the lower extremities. Very few cases of intra-abdominal location have been reported. CASE PRESENTATION: We report a 37 year old man who presented with an abdominal mass and dragging pain. Pre-operative imaging suggested the possibility of a subcapsular hemangioma of liver. CONCLUSIONS: Laparoscopy was useful to locate the tumor as arising from falciform ligament and made the subsequent surgery simpler. This is one of the large fibromyxoid sarcomas to be reported.